Failure analysis and simulation model of pinhole corrosion of the refined oil pipeline. (December 2019) - Feng, Qingshan; Yan, Bingchuan; Chen, Pengchao; Shirazi, Siamack A.
Abstract: A new approach has been developed to conduct failure analysis of pinhole corrosion in pipelines using the normal material failure method and corrosion environment simulations during a full life cycle of the pipeline. A 277 km long DN 355.6 underground pipeline used for the transportation of diesel and gasoline leaked 3 times within 4 years of service. The pipeline had been operating at a 30% permissible capacity with one-third of operation and two-third of shutdown every month. Failure occurred due to internal corrosion at the 3, 4, and6 o'clock positions with respect to the pipeline orientation, resulting in pinholes within 3–4 years of commission. Chemical analysis and metallography were carried out on one of the failed pipeline segments. Various sections of the corrosion products were metallurgically evaluated using scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy. The corrosion product was identified using photometric and potentiometric analyses combined with X-ray diffraction. Diesel, gasoline, and water samples obtained from the pipeline were also analyzed. The material of the pipeline was identified to be X60 with inclusions and manufactured pores. The experimental results indicate that the failure was caused by general corrosion, the activities of sulfate reducing bacteria (SRB), inclusion and/or manufactured pores of pipe body in the environment of chloride, sulfur, and oxygen in water wet at the internal of the pipeline. It is concluded that before the commission, due to the existence of hydrostatic test water, it is easy to cause corrosion of the pipeline. After the commission, along with lower flow velocity and long time shutdown of operation, water deposited to the bottom of pipeline and it is also likely to cause corrosion. The presence of inclusions or small holes in the pipe body accelerates the penetration speed. Series of a pinhole failure caused simulation model and equation of pinhole length were built. The calculation based on the parameters of the failed pinhole is more consistent with the proposed model. Highlights: A new mechanism of pinhole corrosion model is established to describe the root causes of leakages refined oil pipeline. The presence of water, microbes, and manufacturing defects promotes perforation leakage. The corrosion mode and rate of each pipeline stage during construction, commissioning and operation are different. Corrosion rate calculation formula can better verify and predict pipe pinhole corrosion.